Application of GPS technology to assess the demands In soccer competition at college-aged level - Ayllon, F.; Viejo-Romero, D.; Jimenez, A.; Alvar, B. (The Journal of Strength and Conditioning Research, 2010)
The main objective of this study was to describe and quantify the total distance crossed by a group of the College-aged Soccer players during different competition matches, differentiating between the positions in field (defense, midfielder and forward). As second objective, we compare the distance measures in this category with those registered in first class soccer Spanish players (Spanish League and European Champions League). 10 male college-aged soccer players led a global positioning satellite (GPS) device (SPI Elite) for 14 league matches of the season 2008/2009. These devices can measure the distance and calculate the running speed and acceleration made by each player along the match There were 140 entries total. The average distance completed by all players without differentiating the position was 8902.53 +/- 250.4 m, with a range between 7963.5 m and 11161.6 m. When the sample was classified by the position, midfield players completed 9271.34 +/- 130.99 m (p < 0.05), an 8% increase over the defense players (8565.6 +/- 309.5 m) and 4% compared to the forwards players (8870.6 +/- 871.0 m), with no significant differences identified between the last two groups (p > 0.05). The distance completed by college-aged soccer players was significantly lower (p <0.05), than the distance registered from elite level players (Spanish League and European Champions League), where midfield players run 12008.5 +/- 776 m (+22%), the defense players 11405.3 +/- 893 m (+25%) and the forwards players 11254 +/- 894 m (+21 %) Our results are similar to the data showed by other studies which had used other tools, as cameras and tracking system (computerized tracking system) regarding the distance crossed by grade or competition level. Independently of the competition level, the midfielders covered the major distance during the matches The midfielder will require greater attention to Conditioning, especially for the specific endurance capacity, to enable them to cope with the game demands.